Peningkatan Ketahanan Pangan Asal Hewani melalui Olahan Susu Fermentasi di Kelompok Tani Sapi Perah Desa Tumiyang: Improving Animal Food Security through Fermented Milk Processing in the Tumiyang Village Dairy Farmers Group - Setyawardani, Triana; Arkan, Naofal Dhia; Fadhlurrohman, Irfan; Wakhidati, Yusmi Nur; Yusuf, Hasan Muhammad; Tirta, Asmaradika Cahya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Community service activities based on the team's research were carried out through lectures and practical processing methods. Lectures provided theoretical knowledge of milk composition, nutrients, and the health benefits of milk and its processed products. Practical methods were carried out using controlled fermentation technology, optimizing temperature and incubation time, and using commercial starters and kefir grains. The objectives of the activity were (1) transfer of controlled fermentation technology with instant starters to process milk into yogurt, kefir, fermented cheese, and mozzarella cheese; (2) application of the team's research results for the development of easy-to-do, simple, and marketable dairy products; and (3) increasing the empowerment of livestock farmer group members. The results of the community service showed that the highest increase in participant knowledge was in mozzarella cheese products, namely 97.5%, followed by kefir (97%), cottage cheese (95.5%), and yogurt (72.5%). 100% of participants were able to perform the practical processing of the taught products. The resulting products were then sensory tested by a team of semi-trained panelists using the criterion of somewhat liking. The activity concluded that participants increased their knowledge and skills in processing milk-based products, namely yogurt, kefir, mozzarella cheese, and cottage cheese.